Study of double acting cylinder with two in and out piston rods - Duțu, I.C; Axinte, T; Duțu, M.F; Nutu, C; Calancea, L; Diaconu, M (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
This article represents research regarding use of pneumatic double acting cylinder with two in and out piston rods. A cylinder with two in and out piston rods in this paper is a pneumatic actuator. The cylinder with two in and out piston rods works only with compressed air. Besides, the compressed air usually has a pressure of between 2·105 Pa and 6·105 Pa. Cylinder with two in and out piston rods drive with solenoid can be used for various technical applications. In the paper all the circuits have cylinders with two in and out piston rods. These four circuits, simulate the operation of the cylinder with two in and out piston rods. We mention that the pneumatic and electro-pneumatic schemes given in this paper are made using FluidSim software from Festo.